Efficacy of Rituximab Treatment in Vogt-Koyanagi-Harada Disease Poorly Controlled by Traditional Immunosuppressive Treatment. (18th August 2022) - Bolletta, Elena; Gozzi, Fabrizio; Mastrofilippo, Valentina; Pipitone, Nicolò; De Simone, Luca; Croci, Stefania; Invernizzi, Alessandro; Adani, Chantal; Iannetta, Danilo; Coassin, Marco; Fontana, Luigi; Salvarani, Carlo; et al.
ABSTRACT: Purpose: To evaluate the efficacy of Rituximab (RTX) therapy in patients affected by Vogt-Koyanagi-Harada (VKH) disease poorly controlled by traditional immunosuppressive treatment. Methods: Retrospective case series of recurrent VKH uveitis treated with intravenous RTX between January 2019 and November 2020. All patients were treated with intravenous RTX and underwent complete ophthalmic examination, best-corrected visual acuity (BCVA), fundus photography, subfoveal choroidal thickness (SFCT) measurement on enhanced depth imaging optical-coherence tomography (EDI-OCT), fluorescein, and indocyanine green angiography. Results: Five patients were included. All patients received at least 3 RTX infusions. Mean BCVA improved from 20/32 Snellen equivalent at baseline before RTX treatment to 20/28 Snellen equivalent ( p = .008). Mean SFCT on EDI-OCT showed a reduction from 564.4 µm(SD = 176.2) to 280.0 µm(SD = 140.4) ( p = .015). Follow-up ranged from 12 to 21 months, with a mean of 18.2 ± 3.7 months. Conclusions: In these case series, RTX was effective in VHK disease poorly controlled by traditional immunosuppressive treatment.